TEORI NILAI - Abdul Wahab Syakhrani; Nazwa; Tia Hilnanda; Nazwa Saskia; Nadia Putri; Mahmudah (JIP: Jurnal Ilmu Pendidikan, 2026)
Values are an essential part of human life, serving as guidelines that shape attitudes, behaviors, and ways of thinking in distinguishing between right and wrong, good and bad, and appropriate and inappropriate actions. Values are influenced by various factors such as culture, religion, education, and social as well as economic environments, all of which are interconnected in shaping individual character and social harmony. Furthermore, values play a significant role in fostering positive social relationships and developing responsible, honest, and caring individuals. However, in the era of globalization, these values face challenges due to the influence of external cultures that may not align with local values. Therefore, collective awareness is needed to preserve and apply positive values in order to maintain a harmonious and balanced society.